Social Cognition and Obsessive-Compulsive Disorder: A Review of Subdomains of Social Functioning - Jansen, Myrthe; Overgaauw, Sandy; De Bruijn, Ellen R. A. (Frontiers in Psychiatry, 2020)
Disturbances in social cognitive processes such as the ability to infer others’ mental states importantly contribute to social and functional impairments in psychiatric disorders. Yet, despite established social, emotional and cognitive problems, the role of social cognition in obsessive-compulsive disorder is largely overlooked. The current review provides a first comprehensive overview of social (neuro)cognitive disturbances in adult patients with obsessive-compulsive disorder. Results of our review indicate various social cognitive alterations. Patients with obsessive-compulsive disorder show deficits in the recognition of affective social cues, specifically facial expressions of disgust, and more general deficits in theory of mind/ mentalizing. Additionally, patients show heightened affective reactions and altered neural responding to emotions of self and others, as well as poor emotion regulation skills, which may contribute to poor social functioning of patients. However, the discrepancies in findings and scarcity of studies make it difficult to draw firm conclusions with regard to the specificity of social cognitive disturbances. The review offers directions for future research and highlights the need to investigate obsessive-compulsive disorder from an interactive social neurocognitive perspective in addition to the prevalent passive spectator perspective to advance our understanding of this intricate and burdensome disorder.